2021
DOI: 10.1111/jocd.13920
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study between Nd‐YAG laser, fractional CO2 Laser, and combined Nd‐YAG with fractional CO2 Laser in the Management of keloid: clinical and molecular Study

Abstract: Background Fractional CO2 laser and Nd‐YAG laser have been reported to have promising results in the management of keloids. So far, there have been no comparative studies between these laser modalities. Aims The study aimed to compare the efficacy of fractional CO2, Nd‐YAG, and a combination of both in the management of keloids. Patients and methods Forty‐five keloid patients were divided into 3 equal groups: the first received fractional CO2 only, the second received Nd‐YAG only, and the third received a comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Regarding Fitzpatrick skin type, we recorded type III, IV, V skin type in 35%, 50%, 15% of patients respectively. This was near similar to another Egyptian study conducted by Soliman et al (23) who reported that the most common Fitzpatrick Skin type was type IV in 48.9% of the patients with keloid followed by type III in 46.7% of the patients, while type II was the least common in 4.4% of the patients. The Fitzpatrick skin type has a significant impact on the epidemiology of keloids, with incidences ranging from 4.5 percent to 16 percent in type VI to just 0.09 percent in type I (24) .…”
Section: Discussionsupporting
confidence: 91%
“…Regarding Fitzpatrick skin type, we recorded type III, IV, V skin type in 35%, 50%, 15% of patients respectively. This was near similar to another Egyptian study conducted by Soliman et al (23) who reported that the most common Fitzpatrick Skin type was type IV in 48.9% of the patients with keloid followed by type III in 46.7% of the patients, while type II was the least common in 4.4% of the patients. The Fitzpatrick skin type has a significant impact on the epidemiology of keloids, with incidences ranging from 4.5 percent to 16 percent in type VI to just 0.09 percent in type I (24) .…”
Section: Discussionsupporting
confidence: 91%
“…Fractional CO2 laser is reported to be the most effective modality [9]. Fractional CO2 treatment of keloids resulted in a significant decrease in procollagen I compared to Nd:YAG laser and histologically improved arrangement of collagen bundles and increased MMP9 [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…There are 12 items, each with a mean score of 0-2, for a total of 24 points. The studies are categorized by score as "moderate quality" (9)(10)(11)(12)(13)(14)(15)(16) and "high quality" (17)(18)(19)(20)(21)(22)(23)(24). The metaanalysis was performed in accordance with the relevant items in the Preferred Reporting Items for Systematic Reviews and Meta Analyses (PRISMA) statement.…”
Section: Literature Quality Assessmentmentioning
confidence: 99%